2013
DOI: 10.1038/aps.2013.45
|View full text |Cite
|
Sign up to set email alerts
|

A cyclic fluctuation model for 24-h ambulatory blood pressure monitoring in Chinese patients with mild to moderate hypertension

Abstract: Aim:The conventional method for analyzing 24-h ambulatory blood pressure monitoring (24-h ABPM) is insufficient to deal with the large amount of data collected. The aim of this study was to develop a novel cyclic fluctuation model for 24-h ABPM in Chinese patients with mild to moderate hypertension. Methods: The data were obtained from 4 independent antihypertensive drug clinical trials in Chinese patients with mild to moderate hypertension. The measurements of 24-h ABPM at the end of the placebo run-in period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…After a fast release during the first 24 h of assay, 54.28% of CsA and 49.76% of 5-FU were released from PHB microspheres. Similar results by Wang [28] for PHB encapsulation of levonorgestrol were obtained. When microspheres were prepared from PHBHHx, a significant change in the amount of released could be observed.…”
Section: Effect Of Drug and Matrix Materials To Microspheressupporting
confidence: 87%
“…After a fast release during the first 24 h of assay, 54.28% of CsA and 49.76% of 5-FU were released from PHB microspheres. Similar results by Wang [28] for PHB encapsulation of levonorgestrol were obtained. When microspheres were prepared from PHBHHx, a significant change in the amount of released could be observed.…”
Section: Effect Of Drug and Matrix Materials To Microspheressupporting
confidence: 87%
“…As well-known, the alkaloids have a broad spectrum of strong biological activities, but it is generally assumed that quaternary amine type isoquinoline alkaloids are poorly absorbed by gastrointestinal tract such as BB, with up to 5% bioavailability [10,11] and the metabolism occurs in the liver in vivo [12]. In the present study, seven alkaloids from the HLJDT decoction could be detected in the dosed plasma, suggesting that all these alkaloids can be absorbed by gastrointestinal tract into the blood circulation.…”
Section: Plasma Pharmacochemistry Studysupporting
confidence: 47%
“…Seven circadian blood pressure models 28 , 29 , 30 , 31 , 32 , 33 , 34 and four exposure–response models 9 , 11 , 34 , 35 were identified. The model by Trocóniz et al 30 was selected (Table S1 ) over other identified circadian models for different reasons (Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nonlinear mixed‐effects models have been developed as statistical tools that incorporate biological features to understand variability in pharmacological and physiological endpoints 26,27 . Previous efforts have given rise to blood pressure models that capture the various deterministic and stochastic aspects related to blood pressure changes over time 28–34 . In addition, multiple exposure–response models have become available, linking drug TKI exposure to longitudinal changes in blood pressure 9,11,34–36 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation